P-T evolution of metasedimentary rocks of the Santa Filomena Complex, Riacho do Pontal Orogen, Borborema Province (NE Brazil): Geothermobarometry and metamorphic modelling - Santos, Felipe H.; Amaral, Wagner S.; Luvizotto, George L. [UNESP]; Martins de Sousa, Daniel F. (Elsevier, 2018)
We present in this paper petrologic data and discuss the pressure-temperature (P-T) metamorphic history of the neoproterozoic metasedimentary rocks of the Santa Filomena Complex, Riacho do Pontal Orogen, which is inserted in the southern portion of the Borborema Province (Northeast Brazil). Therefore, the data provide constraints on metamorphic evolution during Neoproterozoic Brasiliano Orogeny in Northeast Brazil. The rocks studied are aluminous schists and paragneisses. Silver-gray and red pelitic schists are intensely deformed, biotite-muscovite rich, contain centimeter-sized garnet, staurolite and kyanite porphyroblasts, and subordinately plagioclase and quartz. Paragneisses are from light gray to dark gray colored, medium to coarse-grained and display a well-spaced foliated matrix of biotite, and kyanite and garnet porphyroblasts. Locally, the schists and paragneisses are migmatized. Pressure-temperature modelling based on thermobarometric calculations indicate that metamorphism reached 643 °C with pressures estimated in 12 kbar. Pre-peak and post-peak metamorphic conditions are constrained by mineralogical and textural relationships: garnet inclusion-rich and inclusion-free (possible of higher T) are documented and the inclusion-rich core probably indicates a Sn-1 foliation that was transposed by Sn. The pre-peak stage most probably occurred close to 500 °C and 8 kbar, in upper greenschist to lower amphibolite facies metamorphism along kyanite stability field. We also propose that post-peak stage was associated with isothermal decompression along a possible path of tectonic exhumation in conditions of 600 °C and 7 kbar. To further evaluate the equilibrium condition, pressure-temperature pseudosections were calculated for the metasedimentary rocks. Thus, the estimated metamorphic peak took place in the upper amphibolite facies. A suggested clockwise pressure-temperature path is compatible with the regional tectonic setting of continent-continent collision which occurred in the Late Neoproterozoic of Borborema Province, during the Brasiliano Orogeny.
Keywords: Brasiliano orogeny; Santa filomena complex; Upper amphibolite facies